(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Purchasing decisions are an important aspect for a company. However, various problems that occur that cause purchasing decisions at the company have decreased. Efforts to improve purchasing decisions can be carried out by adjusting prices, service quality and corporate image. The purpose of this study was to determine the effect of price, service quality, and brand image on consumer purchasing decisions at Tailor Citra Clothing in Denpasar, either partially or simultaneously. This research was carried out at Tailor Citra Busana. The population used in this study are all consumers who have run transactions at Tailor Citra Busana in 2020 which reached 257 consumers, with a sample of 72 people. Data were collected by distributing questionnaires which were then analyzed by multiple linear regression. The results of this study provide an illustration that price has a positive and significant effect on purchasing decisions for Tailor Citra Clothing products. Service quality has a positive and significant effect on purchasing decisions for Tailor Citra Clothing products.